Enhanced dielectric deposition on single-layer MoS2 with low damage using remote N2 plasma treatment. (3rd April 2017) - Qian, Qingkai; Zhang, Zhaofu; Hua, Mengyuan; Tang, Gaofei; Lei, Jiacheng; Lan, Feifei; Xu, Yongkuan; Yan, Ruyue; Chen, Kevin J
Abstract: Using remote N2 plasma treatment to promote dielectric deposition on the dangling-bond free MoS2 is explored for the first time. The N2 plasma induced damages are systematically studied by the defect-sensitive acoustic-phonon Raman of single-layer MoS2, with samples undergoing O2 plasma treatment as a comparison. O2 plasma treatment causes defects in MoS2 mainly by oxidizing MoS2 along the already defective sites (most likely the flake edges), which results in the layer oxidation of MoS2 . In contrast, N2 plasma causes defects in MoS2 mainly by straining and mechanically distorting the MoS2 layers first. Owing to the relatively strong MoS2 –substrate interaction and chemical inertness of MoS2 in N2 plasma, single-layer MoS2 shows great stability in N2 plasma and only stable point defects are introduced after long-duration N2 plasma exposure. Considering the enormous vulnerability of single-layer MoS2 in O2 plasma and the excellent stability of single-layer MoS2 in N2 plasma, the remote N2 plasma treatment shows great advantage as surface functionalization to promote dielectric deposition on single-layer MoS2 .